Trait impulsivity during early adolescence predicts steepness of alcohol use escalation across adolescence. (November 2019) - Hamilton, Kristen R.; Felton, Julia W.; Gonçalves, Stefanie F.; Tasheuras, Olivia N.; Yoon, Mark; Lejuez, Carl W.
Abstract: Background and aims: Alcohol use during adolescence is a significant public health concern with serious implications. Both early initiation and rate of escalation of alcohol use during adolescence forecast long-term alcohol-related difficulties and alcohol use disorders (AUDs), underscoring the need to understand psychological factors that contribute to these risk behaviors. One factor that contributes to alcohol use during adolescence is trait impulsivity. The purpose of the present prospective study was to examine associations between trait impulsivity and changes in alcohol use from early adolescence through late adolescence. Methods: Two hundred forty-six participants (45% female; M age = 13.06; 52.5% Caucasian ethnicity) were drawn from a larger study. Levels of impulsivity and alcohol use were measured at every assessment using self-report questionnaires. Data were analyzed using a latent growth modeling approach (LGM) and fit was examined across four indices. Results: Consistent with previous studies, our findings indicate that trait impulsivity decreased and alcohol use increased during adolescence, and initial levels of impulsivity were associated with concurrent levels of alcohol use. Further, level of trait impulsivity during early adolescence predicted the rate of escalation of alcohol use during adolescence. Conclusions: In the present research, trait impulsivity assessed during early adolescence predicted the steepness of alcohol use escalation during adolescence, a variable with significant prognostic value for long-term AUDs and behavioral problems. This research underscores the importance of understanding trait impulsivity during early adolescence, and suggests that early trait impulsivity may have predictive value with respect to later alcohol abuse and behavioral problems. Highlights: Trait impulsivity decreased and alcohol use increased during adolescence. Trait impulsivity during early adolescence was associated with concurrent level of alcohol use. Early trait impulsivity predicted the rate of escalation of alcohol use during adolescence.